1994
DOI: 10.2514/3.12023
|View full text |Cite
|
Sign up to set email alerts
|

Stationary premixed flames in spherical and cylindrical geometries

Abstract: Stationary source-free spherical flames ("flame balls") in premixed combustible gases were studied by employing low-gravity fog) environments in a drop tower and an aircraft flying parabolic trajectories to diminish the impact of buoyancy-induced convective flow. Flame balls were found in all mixture families tested when 1) the Lewis number Le of the deficient reactant was sufficiently low and 2) the compositions were sufficiently close to the flammability limits. Probably as a consequence of the reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 21 publications
3
29
0
Order By: Relevance
“…Flame balls can be stabilized by uniform and constant heat losses only in the burnt gases [6] as well as by relatively weak linear heat losses that nevertheless are of leadingorder importance when temperatures are close to an ambient, far-field value [7]. Non-uniform velocity fields can also stabilize flame balls [8], while non-uniform enthalpy and boundary effects can induce some movement in a stable flame ball [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flame balls can be stabilized by uniform and constant heat losses only in the burnt gases [6] as well as by relatively weak linear heat losses that nevertheless are of leadingorder importance when temperatures are close to an ambient, far-field value [7]. Non-uniform velocity fields can also stabilize flame balls [8], while non-uniform enthalpy and boundary effects can induce some movement in a stable flame ball [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Stable flame balls have been found to arise only when the Lewis number of a lean reactant is less than unity [5][6][7][8][9][10][11][12]. In some sense, the presence of the non-conducting solid can be thought of as adding to the heat capacity of the system, which in turn can be thought of as reducing an effective Lewis number of the two-phase medium as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2 represent the variation with equivalence ratio / ¼ 8Y H 2 1 =Y O 2 1 of the flame-ball radius r f and of the peak temperature T max , with the former plot including also results of experiments [11,12]. To be consistent with the reduced-chemistry results presented below, the value of r f is defined in the numerical computations as the radial location where the temperature takes its crossover value (given approximately by T c ¼ 1000 K at atmospheric pressure, as obtained from Eq.…”
Section: Sample Numerical Resultsmentioning
confidence: 99%
“…as obtained from the seven elementary reactions [11]; solid symbols: [12]), from computations with 21-step chemistry (solid curve) and with one-step chemistry (dashed curve) and from the reaction-sheet analysis (dot-dahed curve).…”
Section: One-step Chemistry Descriptionmentioning
confidence: 99%
“…This concept was further developed by Buckmaster et al [7,8], via asymptotic analysis, showing that, in the presence of heat loss in the near field, the solution with the smaller equilibrium radius is unstable to one-dimensional perturbations while that with the larger equilibrium radius is stable. It was thus suggested that the flame balls observed in experiments carried out in microgravity [9,10] were stabilized by heat loss and that flame balls can be observed only when the Lewis number is smaller than unity [11].…”
Section: Introductionmentioning
confidence: 99%